Phytosociology of the Beech (Fagus) forests in East Asia - Hukusima, Tukasa (Berlin : Springer, 2013)
Phytosociology of the Beech (Fagus) forests in East Asia -- Syntaxonomy of the East Asiatic Fagus forests -- Synthetic remarks -- Appendices.
Includes bibliographical references (pages 255-257).
Keywords: Beech -- East Asia; Forests and forestry -- East Asia